2019
DOI: 10.1080/17470919.2019.1710249
|View full text |Cite
|
Sign up to set email alerts
|

Taking another’s perspective promotes right parieto-frontal activity that reflects open-minded thought

Abstract: 2020) Taking another's perspective promotes right parieto-frontal activity that reflects open-minded thought, Social Neuroscience, 15:3, 282-295, ABSTRACTCritical thinking (CT) is important for consensus building. Although the practice of CT using debate is widely used to improve open-minded thought, the cognitive processes underlying this improvement remain poorly understood. Here, functional magnetic resonance imaging (fMRI) was employed to assess how neural responses while considering another's opinion are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Likewise, it was found that a well-coordinated prefrontal-striatal network that is activated while a subject is experiencing a reward shapes preferences for future choices (Tanaka et al, 2020 ). Also, cognitive appraisal of emotions, belief updating, and self-perspective inhibition has been related to activity in a right fronto-parietal network (Miura et al, 2020 ). As a consequence, the lateral prefrontal cortex participates in the dynamic control of executive actions and in behavioral control (Mansuri et al, 2009 ).…”
Section: Pre-linguistic Processes Of Believingmentioning
confidence: 99%
“…Likewise, it was found that a well-coordinated prefrontal-striatal network that is activated while a subject is experiencing a reward shapes preferences for future choices (Tanaka et al, 2020 ). Also, cognitive appraisal of emotions, belief updating, and self-perspective inhibition has been related to activity in a right fronto-parietal network (Miura et al, 2020 ). As a consequence, the lateral prefrontal cortex participates in the dynamic control of executive actions and in behavioral control (Mansuri et al, 2009 ).…”
Section: Pre-linguistic Processes Of Believingmentioning
confidence: 99%
“…However, adaptive personality traits are rarely associated with higher brain activation in situations where the adaptive nature of the trait is exerted. For example, among other Power to Live subscales, the adaptive trait of problem solving is associated with lower brain activation in motor-related areas ( Miura et al, 2020a ), stubbornness (i.e., resistance to social conformity pressure) in a cognitive control area ( Miura et al, 2020b ), and emotion regulation in extensive cortical regions including the prefrontal control system ( Sugiura et al, 2023 ). The concept of mindfulness ( Bishop et al, 2004 ) may be relevant to adaptive reductions of PCC activity.…”
Section: Discussionmentioning
confidence: 99%
“…In a study in which an MRI task was used to simulate easy or difficult problems in the operation of powerplants, a relationship was found between brain activity involved in coping with difficult problems and problem-solving ( 11 ). In another study, an inverse correlation was reported between neural activation during constructive thinking and stubbornness ( 12 ).…”
Section: Introductionmentioning
confidence: 90%